Empowering Rural Communities through Strengthening Village-Owned Enterprises (BUMDes) for Sustainable Socioeconomic Development: A Case Study of Mekarsari Village, Garut Regency - Pawitan, Gandhi; Lesmono, Dharma; Aritonang, Kinley; Diyanah, Mumsikah Choyri (Society, 2025)
Strengthening Village-Owned Enterprises (BUMDes) is crucial for reducing economic disparities in rural areas and promoting sustainable community development. While previous studies have primarily focused on financial structures and regulatory frameworks, this research adopts a participatory approach that actively engages local stakeholders in capacity-building efforts. Using BUMDes Mekarsari in Garut Regency as a case study, the study examines how participatory strengthening programs enhance the socio-economic resilience of rural communities. Employing qualitative methods—including in-depth interviews and field observations—it identifies key factors influencing BUMDes effectiveness, such as continuous training, institutional collaboration, and improved access to finance. The findings reveal that a participatory model not only fosters community engagement but also improves business sustainability and expands economic opportunities. In particular, the involvement of women and local artisans demonstrates the program’s inclusivity and potential for social transformation. Moreover, the integration of digital marketing strategies has opened new market access, further supporting rural entrepreneurship. To maximize practical impact, the study offers concrete policy recommendations, including strengthening institutional support for BUMDes, fostering multi-sector partnerships, and enhancing financial accessibility through local and national policies. These insights contribute to a more inclusive framework for rural economic empowerment, providing policymakers with a strategic foundation for designing community-driven BUMDes programs that ensure their long-term success as catalysts for local development.